Synthesis and biological evaluation of new 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Nawale, Laxman; Sarkar, Dhiman (Research on Chemical Intermediates, 2018)
A series of 2-aryl-4-((4-aryl-1H-1,2,3-triazol-1-yl)methyl)thiazole derivatives (8a-p) have been synthesized. The structure of the newly synthesized compounds was determined by spectral analysis. The title compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Further, the synthesized compounds were screened for antimicrobial activity against standard Gram-negative bacteria Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059) and Gram-positive bacteria Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162). Among all the synthesized compounds, 8a-c, f-h, m exhibited good activity against dormant M. bovis BCG strain. Compounds 8h, j exhibited good activity against all tested bacterial strains. All active compounds were screened for cytotoxicity and found inactive. Their high potency and promising antimycobacterial activity suggest that these compounds could serve as good leads for further optimization and development.
Keywords: 1; 2; 3-Triazole; antibacterial activity; Antitubercular activity; Thiazole

Synthesis and antimycobacterial evaluation of new 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives - Shinde, Vikas; Mahulikar, Pramod; Mhaske, Pravin C.; Chakraborty, Shakti; Choudhari, Amit; Phalle, Siddharth; Choudhari, Prafulla; Sarkar, Dhiman (Medicinal Chemistry Research, 2019)
A new series of 5-(1-benzyl-1H-1,2,3-triazol-4-yl)-4-methyl-2-arylthiazole derivatives, 6a-w have been synthesized by click reaction of substituted benzylazide, 5a-d with 5-ethynyl-4-methyl-2-substituted phenylthiazole, 4a-f. The starting compounds 4-ethynyl-2-substituted phenylthiazole (4a-f) were synthesized from the corresponding thiazole aldehyde by using the Ohira-Bestmann reagent. The structure of the synthesized compounds was determined by spectral analysis. All the synthesized compounds were screened for their preliminary antitubercular activity against Mycobacterium tuberculosis H37Ra (MTB, ATCC 25177). Most of the synthesized compounds reported good activity against M. tuberculosis H37Ra strain with IC50 range of 0.58-8.23 mu g/mL. Compounds 6g and 6k reported good antitubercular activity with MIC90 values of 4.71 and 2.22 mu g/mL, respectively. Potential antimycobacterial activity suggested that these compounds could serve as good lead compounds for further optimization and development of a newer antitubercular candidate. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; Antitubercular activity; Molecular docking; Ohira-Bestmann reagent; Thiazole

Synthesis and biological evaluation of new 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-phenylthiazole derivatives - Shinde, Vikas; Mhaske, Pravin C.; Singh, Aakriti; Sarkar, Dhiman; Mahulikar, Pramod (Journal of Heterocyclic Chemistry, 2019)
A novel series of 4-(4-(1-benzyl-1H-1,2,3-triazol-4-yl)phenyl)-2-substitutedthiazole derivatives (8a-l) have been synthesized by [3 + 2] cycloaddition reaction of 4-(4-ethynylphenyl)-2-substitutedthiazole with substituted benzyl azide in aqueous DMF. Starting compounds 4-(4-ethynylphenyl)-2-substitutedthiazole (6a-d) were synthesized by reaction of 4-(2-substitutedthiazol-4-yl)benzaldehyde with Ohira-Bestmann reagent in methanol. The structures of these novel triazole-thiazole clubbed derivatives were confirmed by the spectral analysis. The title compounds (8a-l) were tested for antimycobacterial activity against Mycobacterium tuberculosis H37Ra active and dormant (MTB, ATCC 25177) and antimicrobial activity against standard Gram-positive bacteria, Staphylococcus aureus (NCIM 2602) and Bacillus subtilis (NCIM 2162), and Gram-negative bacteria, Escherichia coli (NCIM 2576) and Pseudomonas flurescence (NCIM 2059). Compounds 8a, 8b, 8c, and 8h reported good activity against B subtilis, compounds 8a, 8b, and 8c showed good activity against S aureus, and compound 8b showed good activity against dormant M tuberculosis H37Rv strain. Compounds 8b and 8c found more potent against Gram positive and dormant M tuberculosis H37Rv strains. These novel triazole-thiazole clubbed analogues found to be a capable leads for further optimization and development.